Implementasi Metode Waspas Dalam Menyeleksi Posisi Chief Staff Pada Pt. Codinglab Dengan Metode Pembobotan Roc - Amanudin Harahap (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
PT. CodingLab Medan within a certain period of time always evaluates the performance of its employees. The results of the performance appraisal will then be processed in the selection of promotions, including the position of Chief Staff. However, in evaluating the performance appraisal of PT. CodingLab employees, the process is still done manually (based on the owner's assessment). So that the results of the assessment can result in an inaccurate and subjective assessment. Based on the problems described above, a Decision Support System (DSS) is needed which is expected to help existing problems because of the weight of the values used, the selection process can be more effective and optimal. In addition, SPK makes it easier to evaluate employee performance. The ROC and WASPAS methods are very suitable to be used in the process of selecting employees by developing a website-based information system that makes it easier for users to carry out their activities. The results of this study indicate that with the decision support system (DSS) which was built with a combination of the ROC and WASPAS methods, PT. Codinglab Medan can conduct an assessment of employees so that they can select the position of chief staff more quickly, precisely and objectively.